2019
DOI: 10.4067/s0717-97072019000404610
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a Chitosan-Based Citric Acid-Crosslinked Encapsulant System

Abstract: An encapsulant system was prepared via crosslinking of chitosan using citric acid as a crosslinker. FTIR spectroscopy, particle size and zeta potential analyses confirmed successful crosslinking, appropriate particle size and colloidal stability. Encapsulation capability of the said material was investigated using fluorescence spectroscopy. The effect of pH on the crosslinked chitosan particles was also conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…These indicate the symmetric and asymmetric stretching vibrations of the C=O bond in metal carboxylates, thereby confirming the chelation of metal ions by citric acid [31,44,46]. For the G-G gel, a characteristic peak was observed at 1725 cm −1 , which was not observed for G-W or G-E; this indicated the formation of the cross-linked polymer, and it is obvious that ethylene glycol was polymerized by cross-linking the ester through two carboxyl groups [47]. In comparison, it can be concluded that the ν a(COO)…”
Section: Mechanism Of Sol-gel Synthesismentioning
confidence: 81%
“…These indicate the symmetric and asymmetric stretching vibrations of the C=O bond in metal carboxylates, thereby confirming the chelation of metal ions by citric acid [31,44,46]. For the G-G gel, a characteristic peak was observed at 1725 cm −1 , which was not observed for G-W or G-E; this indicated the formation of the cross-linked polymer, and it is obvious that ethylene glycol was polymerized by cross-linking the ester through two carboxyl groups [47]. In comparison, it can be concluded that the ν a(COO)…”
Section: Mechanism Of Sol-gel Synthesismentioning
confidence: 81%
“…It is important to state that CHI solution was used as solvent in the defibrillation step of cellulose, and this is known to produce stronger interaction compared to a simple mixing after defibrillation and a very well mixed film without concentrated spots is seen using this methodology [28]. However, no new peaks were seen around region 1700 cm −1 , which is a region reported by Agu et al of crosslinking confirmation by citric acid [13].…”
Section: Chi Blended With Nfcmentioning
confidence: 95%
“…This study aims to analyse the effect of various films formed with CHI and blended with nanofibrillated cellulose (NFC) and polyvinyl alcohol (PVA), using citric acid as a crosslinker that is known to produce an encapsulation ability for CHI; also, it could provide important mechanical properties and functional desirable outcomes [13].…”
Section: Introductionmentioning
confidence: 99%
“…3). The peaks obtained at 1730 cm -1 is corresponding to the C=O of ester linkage [15]. After loading of chlorpyrifos, some new interactions between biopolymeric nano-formulation and chlorpyrifos has been established, which resulted into slight shifting and splitting of peak corresponding to ester linkage from 1730 cm -1 to 1691 cm -1 .…”
Section: Ft-ir Studiesmentioning
confidence: 97%